CULTURE-BASED BRAIN GYM: MULTIETHNIC STUDENTS, CULTURE IDENTITY AND TEACHERS ROLE IN WEST JAVA - Annisa, Nuri; Sunendar, Dadang; Agustin, Mubiar; Puspitasari, Rianita (PD PGMI se Indonesia, 2025)
This study aims to examine the role of teachers in strengthening national identity among multiethnic students in West Java and the effectiveness of culture-based Brain Gym in supporting the process. Qualitative research methods were used with data collection through written tests, questionnaires, in-depth interviews, and participant observations of teachers and students in five elementary schools in Bandung. The findings indicate that students' low interest in local culture due to the dominance of foreign culture can be overcome by integrating traditional cultural elements (music, dance, and visualization) into a series of Brain Gym movements. Teachers who systematically facilitate these activities can create an interactive and meaningful learning atmosphere, thus triggering emotional responses and increasing awareness of local culture among students. In addition to enriching the learning experience and balancing physical-mental activities, this approach has proven effective in strengthening a sense of pride in cultural heritage and supporting the formation of an inclusive national identity. Thus, implementing a culture-based Brain Gym, combined with the active role of teachers as facilitators and motivators, is recommended as an innovative learning strategy to strengthen cultural literacy and national identity in elementary schools.